Mobile Phone Harassment: An Exploration of Students' Perceptions of Intrusive Texting Behavior - Short, Emma; McMurray, Isabella (Human Technology, 2009)
Limited research has explored the link between mobile phone use and harassment behaviors. This paper details the findings from a preliminary study that examined perceptions of unwanted communication, with one focus group (7 participants) and two vignettes presented to 145 students. The vignette participants were asked to respond to hypothetical questions about continued and unwanted contact being maintained as if they were both a sender and recipient of the contact and if they had actually been harassed. Response options allowed for intended behavior to be measured against generally agreed thresholds of duration and frequency used to identify harassment. Findings indicated that harassment by text is more prevalent than other forms of off-line stalking and, despite recipients reporting being distressed, there was still a higher level of acceptance of this form of harassment than other forms. Furthermore, responses to text harassment were associated with a high frequency of behaviors perceived as not actively discouraging further texts, therefore having the effect of prolonging unwanted contact. These results are discussed in relation to intervention strategies and future research.